Determinants of an optimal practice of caesarean section in Western African countries - (:unkn) unknown (My University, 2017)
In Burkina Faso, the national caesarean section rate is still low (2% in 2012). However, since the introduction of caesarean user fee exemption in 2006 and the availability of trained staff to perform a caesarean section in the most remote hospitals, the institutional caesareans rates have risen steadily and it is unclear whether all of these interventions are necessary. The main objective of this thesis is to identify the determinants of an optimal practice of caesarean section in three western African countries that favour access to caesarean section. The results of the work carried out in the framework of this thesis show that the level of qualification of the health personnel working in Burkina Faso hospitals and his professional experience determine globally his level of knowledge in the management of labor and complicated childbirth. . In addition, regular supervision of his work by daily review of clinical records (partograms) seems to improve his performance. The level of qualification of health personnel in Burkina Faso also influences the practice of non-medically justified caesareans. But the social environment also plays a role in this abusive practice. The results of this research show that the systematic practice of cesarean section after an anterior caesarean section is not justified in this context. The results of this thesis led to the development and implementation of a multi-faceted intervention trial aimed at reducing caesareans without medical reason in West Africa.
Keywords: African Research